From Intuitive Practice to Intentional Pedagogy: Subitization in Wetland-Based Early Childhood Education - Novitawati, Novitawati; Doddyansyah, Muhammad Rusvendy; Auliya, Alfiana Falan Syarri; Fitria, Fadilatul (THUFULA, 2026)
Subitization is an important aspect of early numeracy that enables children to recognize small quantities without counting and serves as a foundation for number sense development. Although wetland environments provide rich opportunities for contextualized numeracy learning, their potential remains underutilized in many early childhood education settings. This study investigated teachers’ understanding and implementation of subitization-related activities and explored the extent to which wetland contexts are incorporated into early numeracy learning. Using a qualitative case study design, data were collected through interviews and classroom observations involving teachers from Pembina Inti Kindergarten in Banjarmasin, Indonesia. Data were analyzed through condensation, display, and conclusion drawing. The findings reveal that teachers regularly engage children in activities that support subitization, such as dice, domino, and object-recognition games. However, they do not explicitly identify these practices as subitization. This indicates a gap between intuitive classroom practice and intentional pedagogical understanding. In addition, wetland resources and experiences are rarely integrated into numeracy activities despite their relevance to children’s local environment. The study highlights the need for professional development and curriculum support to bridge intuitive practice and intentional pedagogy in subitization learning and to promote the meaningful integration of wetland contexts into early childhood numeracy education.